High-intensity-exercise-induced intestinal damage is protected by fermented milk supplemented with whey protein, probiotic and pomegranate (Punica granatum L.). Issue 8 (12th April 2018) - Chaves, Fernanda M.; Baptista, Igor L.; Simabuco, Fernando M.; Quaresma, Paula G. F.; Pena, Fabiola L.; Bezerra, Rosangela M. N.; Pauli, Jose R.; da Cunha, Diogo T.; Campos-Ferraz, Patricia L.; Antunes, Adriane E. C.
Abstract: Here we evaluated the effect of fermented milk supplemented with whey protein (approximately 80 % protein), probiotic ( Bifidobacterium animalis subsp. lactis BB12) and pomegranate juice ( Punica granatum L.) on the physical performance, intestinal motility and villi structure, inflammatory markers and intestinal microbiota of rats under high-intensity acute exercise. In all, twenty-four Wistar rats were separated into groups: control (Ctrl), supplemented (Supp), exercised (Exe) and exercised and supplemented (Exe+Supp). Rats in the Supp groups received fermented milk during 6 weeks by oral administration. At the end of the supplementation period, the Exe groups were submitted to high-intensity acute exercise on a treadmill. We found that intense acute exercise caused changes in the intestinal villi interspace, changes in the proportion of Lactobacillus species and an increase in Clostridium species, as well as a decrease in intestinal motility. Supplementation increased intestinal motility, and maintained the intestinal villi interspace and the natural microbiota proportions of the exercised rats. Physical performance was not improved by fermented milk supplementation. We conclude that the fermented milk containing whey protein, B. animalis (BB12) and pomegranate juice can re-establish intestinal microbiota and protect the animals from the undesirable effects of intense acute exercise.